From the pedagogical to the psychoanalytical act: contributions about the "education and its discontents" question - Voltolini, Rinaldo (Clinical Styles. The Journal on the vicissitudes of childhood, 2001)
In this paper we expose questions and discussions about the concept of "education and its discontents". The aim of this study is to think about the possibility of a psychoanalytical act in this context. We work with the Lacan's theory of the four discourses and the notion of social sympthom in order to treat the kind of things that makes discontents in school institution.